Effects of intraocular miotics on cultured bovine corneal endothelium. Issue 12 (December 1978) - Jay, J L; MacDonald, M
Abstract : Two cases of severe corneal oedema occurred after the use of intraocular pilocarpine. Experimental investigations were conducted with cultured bovine corneal endothelial cells exposed for 5 minutes to 1% pilocarpine solutions of varying composition. Cells were destroyed in solutions not isotonic with aqueous humour, and calcium-free ionic solutions caused loss of cell adhesion without loss of viability. Low pH or the presence of 1% pilocarpine had no detectable effects; 1% acetylcholine chloride in 5% mannitol (Miochol) also caused cell destruction, and this preparation was found to be considerably hypertonic. The minimum requirements for the formulation of intraocular miotics are discussed.